2018
DOI: 10.1200/jco.2017.74.1173
|View full text |Cite
|
Sign up to set email alerts
|

Role of Genetic Testing for Inherited Prostate Cancer Risk: Philadelphia Prostate Cancer Consensus Conference 2017

Abstract: Guidelines are limited for genetic testing for prostate cancer (PCA). The goal of this conference was to develop an expert consensus-driven working framework for comprehensive genetic evaluation of inherited PCA in the multigene testing era addressing genetic counseling, testing, and genetically informed management. MethodsAn expert consensus conference was convened including key stakeholders to address genetic counseling and testing, PCA screening, and management informed by evidence review. ResultsConsensus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
142
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(152 citation statements)
references
References 58 publications
2
142
0
1
Order By: Relevance
“…Other germline variants were detected in ethnic groups 9,10 . Recently, a consensus conference has recommended testing HOXB13 for suspected hereditary Pca 11 …”
Section: Introductionmentioning
confidence: 99%
“…Other germline variants were detected in ethnic groups 9,10 . Recently, a consensus conference has recommended testing HOXB13 for suspected hereditary Pca 11 …”
Section: Introductionmentioning
confidence: 99%
“…Germline genetic testing for men with PCA is rapidly rising with expansion of guidelines and expert opinion, along with increasing treatment and clinical trial options . Prior studies have reported germline pathogenic variants particularly in DNA repair genes among men selected for advanced/metastatic disease or based on strict family history criteria, leaving a gap regarding the germline spectrum and potential clinical impact from multigene testing among men unselected for metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic testing for inherited prostate cancer (PCA) is increasing with expansion of genetic testing guidelines and increasing capability of clinical multigene testing . The NCCN Genetic/Familial High‐risk Assessment: Breast and Ovarian (Version 2.2019) recommends BRCA testing for men with metastatic PCA or men with Gleason score>= 7 who have any of the following: (1)>= 1 close blood relative with ovarian, pancreatic, metastatic PCA, or breast cancer at age <50, (2) > = 2 close blood relatives with breast or prostate cancer at any age, or (3) Ashkenazi Jewish ancestry .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations